Pilot study suggests DNA methylation of the glucocorticoid receptor gene (NR3C1) is associated with MDMA-assisted therapy treatment response for severe PTSD - Lewis, Candace R.; Tafur, Joseph; Spencer, Sophie; Green, Joseph M.; Harrison, Charlotte; Kelmendi, Benjamin; Rabin, David M.; Yehuda, Rachel; Yazar-Klosinski, Berra; Cahn, Baruch Rael (Frontiers in Psychiatry, 2023)
Background: Previous research has demonstrated that epigenetic changes in specific hypothalamic-pituitary-adrenal (HPA) genes may predict successful psychotherapy in post-traumatic stress disorder (PTSD). A recent phase 3 clinical trial reported high efficacy of 3,4 methylenedioxymethamphetamine (MDMA)-assisted therapy for treating patients with severe PTSD compared to a therapy with placebo group (NCT03537014). This raises important questions regarding potential mechanisms of MDMA-assisted therapy. In the present study, we examined epigenetic changes before and after MDMA and placebo with therapy. As a pilot sub-study to the parent clinical trial, we assessed potential HPA epigenetic predictors for treatment response with genomic DNA derived from saliva (MDMA, n = 16; placebo, n = 7). Methylation levels at all 259 CpG sites annotated to three HPA genes (CRHR1, FKBP5, and NR3C1) were assessed in relation to treatment response as measured by the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5; Total Severity Score). Second, group (MDMA vs. placebo) differences in methylation change were assessed for sites that predicted treatment response. Results: Symptom reduction across groups significantly correlated with HPA DNA methylation changes on 37 of 259 CpG sites tested, with two sites surviving false discovery rate (FDR) correction. Further, the MDMA-treatment group showed more methylation change compared to placebo on one site of the NR3C1 gene. Conclusions: The findings of this study suggest that therapy-related PTSD symptom improvements may be related to DNA methylation changes in HPA genes and such changes may be greater in those receiving MDMA-assisted therapy. These findings can be used to generate hypothesis driven analyses for future studies with larger cohorts.